The Effects of Collaborative Learning on Young ESL Learners’ L2 Anxiety and Speaking Performance - Thi Yen Nhi Ha; Thi Bich Ngoc Nguyen; Ngoc Lynh Dan Nguyen; Trung Nghia Tran (International Journal of Asian Education, 2022)
Foreign Language Anxiety (FLA) is one of the issues of interest attracting researchers in recent decades. However, while collaborative learning introduced a prospective tool for FLA, it has not been much researched in the L2 classroom context, particularly in Vietnam. This paper focuses on using collaborative learning to reduce foreign language anxiety and enhance the L2 speaking performance of young learners at an English center in Ho Chi Minh City. A combination of tools, including Aydin et al.’s (2017) Children Foreign Language Anxiety Scale (CFLAS) for the pre-tests and post-tests, the teacher’s diary, and follow-up interviews, was used to measure the changes in learner’ FLA level and speaking performance. After five-week implementations, these learners’ FLA was slightly alleviated, and their speaking performance was improved using a collaborative learning approach. Moreover, learners were found to have positive attitudes and experience with learning in the new approach. These findings implied that collaborative learning could be a potential treatment to help L2 learners uncover their anxious selves and find more confidence in using the target language